Investigation into Teachers’ European Competences - Jucevičienė, Palmira (Pedagogika, 2017)
Nowadays, more than ever before, development of the European competences has become extremely important. These competences are especially significant for the young generation, thus they became an important field for education researchers. The European competences are of particular importance to teachers who not only use them as citizens, but also influence others to develop them. In order to develop the European competences Europe as a learning environment is necessary and it is being purposefully developed: the European Commission has established a broad range of programmes which help teachers to develop the necessary competences. Projects in the area have produced a significant amount of knowledge as asset which may be and is applied for the better Europe. The knowledge has become an open source of information for the teachers in the development of their European competences. The aim of the current paper is to reveal what specific European competences teachers from EU countries recognize by self-reflection as an “asset in-use” in their professional daily lives. A survey was used as the main research method supported by the analysis of the scholarly literature.